The trial of Abigail Goodman - Fast, Howard 1914-2003 (Crown Publ., 1993)
A New York woman is charged with murder under a law that retroactively makes abortion a capital offense.
Keywords: Trials (Abortion) -- Fiction; Legal stories; Mystery fiction